Model Terapi Latihan Pasca Cedera Ankle pada Atlet Taekwondo Klub KBTC - Mertha Elistya Kurniawan; Yasep Setiakarnawijaya; Fahmy Fachrezzy (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to create and develop a form of exercise therapy after ankle injury that can help recovery. Activities that have been carried out using the RND method will produce a product in the form of a model of exercise therapy after ankle injury. Subjects who were targeted in research on the development of post-injury exercise therapy models for KBTC club taekwondo athletes. Of the ten steps of Sugiyono's research model, this research only reaches the sixth stage, namely: (1) potential and problems, (2) data collection, (3) initial product design, (4) design validation, (5) design revision, (6) Product trial. The results of this action research will produce a complete exercise therapy design product that is more specific to the sport of taekwondo.In this study, researchers collaborated with experts in the field of physiotherapy, experts in injury management as expert judgment. The validation test used in this study used an expert justification test, where the exercise therapy model after ankle injury used 14 validated models.This post-ankle injury exercise therapy model can also be used as reference material for other researchers in post-ankle injury exercise therapy in KBTC club athletes. The results of this research can be concluded that after going through validation tests with expert justification, 14 models of post-ankle injury training therapy models were produced for KBTC club taekwondo athletes.